Stress biomarkers in minimally invasive and conventional colorectal resections. Issue 3 (4th May 2019) - Netto, Jeffrey; Jansen-Winkeln, Boris; Thieme, René; Eckardt, Jan; Ju Bae, Yoon; Willenberg, Anja; Huppert, Sabine; Lyros, Orestes; Niebisch, Stefan; Allecke, Friederike; Kreuser, Nicole; Kratzsch, Jürgen; et al.
Abstract: Introduction: Any surgical procedure develops a stress situation for the patient, which can modulate the individual outcome. At present, there is only limited information about stress response in colorectal resections by laparoscopic compared to conventional surgery. Therefore, our objectives were the feasibility and the investigation of stress biomarkers including copeptin and steroid hormones before, during and after colorectal surgery. Methods: Eleven patients underwent minimally invasive and ten patients conventionally open colorectal surgery. Blood samples were collected before, during and 24 h after surgery and copeptin, NT-proBNP, cortisol, cortisone, interleukin-6 and glucose were analyzed. Results: Both, minimally invasive and conventional-open colorectal surgery caused a fast but heterogeneous response of stress biomarkers. However, the postoperative decrease of cortisol, cortisone and glucose differed between both groups. The stress biomarkers decreased faster down to baseline after minimally invasive surgery, while in open surgery cortisol, cortisone and glucose did not return to baseline within 24 h after operation. Conclusions: We show in this feasibility study for the first time an increase of copeptin in combination with glucocorticoids as stress biomarkers by open surgery compared to minimally invasive procedures in patients undergoing colorectal surgery. Exceeding an individual threshold of 'stress burden' may have unfavorable effects on the long-time clinical outcome.